Parenting Practices: A Study On How Nuclear Parents Handle Their Teenager’s Sexuality - Cuenca, Suyen Mayumi R. (Animo Repository, 2023)
Parents can represent the world to a child. As a result, a child may attempt to imitate their parents' behavior or react strongly to their discipline or rewards. Thus, a parent's parenting style can considerably influence their child's growth. Adolescents in the twenty-first century are experiencing the emergence of their sexual and gender identities as our society is constantly evolving and challenging standards. As a result, the researchers aim to determine how nuclear parents handle their teenager's sexuality. This phenomenological study collects data on the parenting styles of participants through interviews and classifies them in accordance with the core parenting styles of the Philippines. The findings of this study will also serve as a guide for determining whether or not the strategies and approaches that parents use to care for their teenagers are beneficial from the teenagers' points of view. The results were separated into two categories: narratives from nuclear parents and narratives from teenagers. The parent narratives revealed four (4) superordinate themes: parental response, parental strategy, parent-teen relationship, and parenting styles. And two (2) superordinate themes for teenagers: factors of coming out and teenagers' perspective.